2021
DOI: 10.1093/qjmed/hcab014
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapies and checkpoint inhibitors in sarcoma

Abstract: Sarcomas are defined as a group of mesenchymal malignancies with over 100 heterogeneous subtypes. As a rare and difficult to diagnose entity, micrometastasis is already present at the time of diagnosis in many cases. Current treatment practice of sarcomas consists mainly of surgery, (neo)adjuvant chemo- and/or radiotherapy. Although the past decade has shown that particular genetic abnormalities can promote the development of sarcomas, such as translocations, gain-of-function mutations, amplifications or tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 128 publications
0
6
0
Order By: Relevance
“…Of note, the expression levels of immune checkpoint proteins and tumor antigens within TLS determine the immune response in TLS. Common checkpoint proteins include PD‐1, CTL‐associated antigen‐4 (CTLA‐4), T cell immunoglobulin (TIM), lymphocyte‐activation gene 3 (LAG‐3) 70 . PD‐1 affects the activity of effector T cells, 71 while CTLA‐4 affects the initial activation.…”
Section: Forming Process and Immune Mechanisms Of Tlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the expression levels of immune checkpoint proteins and tumor antigens within TLS determine the immune response in TLS. Common checkpoint proteins include PD‐1, CTL‐associated antigen‐4 (CTLA‐4), T cell immunoglobulin (TIM), lymphocyte‐activation gene 3 (LAG‐3) 70 . PD‐1 affects the activity of effector T cells, 71 while CTLA‐4 affects the initial activation.…”
Section: Forming Process and Immune Mechanisms Of Tlsmentioning
confidence: 99%
“…Common checkpoint proteins include PD‐1, CTL‐associated antigen‐4 (CTLA‐4), T cell immunoglobulin (TIM), lymphocyte‐activation gene 3 (LAG‐3). 70 PD‐1 affects the activity of effector T cells, 71 while CTLA‐4 affects the initial activation. Though CTLA‐4 is principally expressed on CD8+ T cells, its blockade mainly interferes with 2 T cell subsets: extends the T helper cell‐dependent immune responses, and downregulates the immune‐suppressive effects of Tregs.…”
Section: Forming Process and Immune Mechanisms Of Tlsmentioning
confidence: 99%
“…With over 100 distinct subtypes, these tumors can manifest in multiple anatomical sites. Due to its rarity and diagnostic challenges, metastasis often transpires during the underdiagnosed disease stage 1 . However, the survival rate for localized sarcoma can become 70–75% by employing a comprehensive approach associated with systemic therapy, chemotherapy, and effective management of the primary tumor via surgery and/or radiation 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the tumor compensatory AGING mechanism, tumor heterogeneity and complex tumor microenvironment (TME), targeted therapy for sarcomas is limited to partial tumor subtypes [5]. As tumor research has progressed, TME has shown a notable impact on the progression of sarcomas, and immunotherapy has become a novel therapeutic choice for sarcomas [6,7]. Therefore, it is particularly important to identify new biomarkers and understand their importance in TME for finding new potential therapeutic strategies of sarcomas and improving the prognosis of sarcoma patients [8].…”
Section: Introductionmentioning
confidence: 99%